Repetitive Transcranial Direct Current Stimulation Induced Excitability Changes of Primary Visual Cortex and Visual Learning Effects—A Pilot Study - Sczesny-Kaiser, Matthias; Beckhaus, Katharina; Dinse, Hubert R.; Schwenkreis, Peter; Tegenthoff, Martin; Höffken, Oliver (Frontiers in Behavioral Neuroscience, 2016)
Studies on noninvasive motor cortex stimulation and motor learning demonstrated cortical excitability as a marker for a learning effect. Transcranial direct current stimulation (tDCS) is a non-invasive tool to modulate cortical excitability. It is as yet unknown how tDCS-induced excitability changes and perceptual learning in visual cortex correlate. Our study aimed to examine the influence of tDCS on visual perceptual learning in healthy humans. Additionally, we measured excitability in primary visual cortex (V1). We hypothesized that anodal tDCS would improve and cathodal tDCS would have minor or no effects on visual learning. Anodal, cathodal or sham tDCS were applied over V1 in a randomized, double-blinded design over 4 consecutive days (n = 30). During 20 minutes of tDCS, subjects had to learn a visual orientation-discrimination task. Excitability parameters were measured by analyzing paired-stimulation behavior of visual-evoked potentials (ps-VEP) and by measuring phosphene thresholds before and after the stimulation period of 4 days. Compared with sham-tDCS, anodal tDCS led to an improvement of visual discrimination learning (p < 0.003). We found reduced phosphene thresholds and increased ps-VEP ratios indicating increased cortical excitability after anodal tDCS (phosphene threshold: p = 0.002, ps-VEP: p = 0.003). Correlation analysis within the anodal tDCS group revealed no significant correlation between phosphene thresholds and learning effect. For cathodal tDCS, no significant effects on learning or on excitability could be seen. Our results showed that anodal tDCS over V1 resulted in improved visual perceptual learning and increased cortical excitability. tDCS is a promising tool to alter V1 excitability and, hence, perceptual visual learning.